Dynamic landscape of transcription initiation by yeast RNA polymerase I - Parilova, Olena; Bartos, Piia; Malinen, Anssi M. (Oxford University Press (OUP), 2026)
RNA polymerase I (Pol I) synthesizes precursor ribosomal RNA, a key step in ribosome biogenesis. Elevated Pol I activity supports rapid cell growth—a hallmark of cancer—making Pol I a therapeutic target. The initial step in synthesis involves assembly of the Pol I transcription initiation complex on the gene promoter; however, its quantitative and dynamic parameters remain poorly defined. Here, we integrate biochemical, biophysical, and molecular dynamics approaches to dissect promoter and transcription start site (TSS) recognition by the Saccharomyces cerevisiae Pol I machinery. We show that core factor (CF) identifies the promoter through a two–step mechanism: a rapid encounter is followed by a slower conformational transition that establishes stabilizing interactions. In contrast, CF binds nonpromoter DNA in a single step without such transitions, forming nonspecific complexes that dissociate quickly. Correct promoter binding allows CF to recruit and position Pol I near the TSS, inducing DNA bending, helix distortion, and melting as the preinitiation complex converts into an active state. These functional and dynamic parameters contribute to a quantitative framework for elucidating the molecular mechanisms of Pol I regulation and inhibition.